ChokeSafe: Empowering Children with Life-Saving Choking-Management Skills - Eleana Tse; Katerina Plakitsi; Spyridon Voulgaris; George A. Alexiou (MDPI AG, 2024)
Choking stands as the fourth leading cause of unintentional injury deaths. This research aimed to evaluate the ability of young schoolchildren to grasp and remember choking-management techniques, as well as to compare the effectiveness of instructors. We conducted a randomized controlled trial to assess the impact of choking training on young children. We randomly selected 180 children aged 4-8 years and divided them into a training group (120 children) and a control group (60 children). We evaluated the students' response to a choking incident with a specific scenario one day before, one day after, and two and seven months after the training, as well as once to the control group. Before the training, there was no significant difference between the groups. However, after the training, the training group's scores showed a significant increase compared to their pre-training scores and those of the control group. Even at two- and seven-month post-training, the training group's scores had decreased but remained higher than their pre-training scores and those of the control group. Choking training can benefit young children. Our research highlights the equal importance of both regular classroom teachers and specialized personnel in imparting these essential skills. However, further research is necessary to confirm these observations and explore methods for sustaining the acquired knowledge from the training.